Highly Fluorescent Nanotubes with Tunable Diameter and Wall Thickness Self‐Assembled from Asymmetric Perylene Diimides. Issue 32 (4th July 2016) - Peng, Cheng; Zhang, Yibin; Zhang, Yifan; Hu, Yanyong; Che, Yanke; Zhao, Jincai
Abstract : Highly fluorescent bilayer‐walled and monolayer‐walled nanotubes are assembled from elaborately designed asymmetric perylene diimide (PDI) molecules. The diameter of bilayer‐walled nanotubes increases with the size of the branched substituents at the meta‐position of the phenyl moiety of PDI molecules, whereas that of monolayer‐walled nanotubes remains unchanged regardless of the size of branched substituents.